Genome analysis of Erwinia persicina reveals implications for soft rot pathogenicity in plants - Wasendorf, Chloe; Schmitz-Esser, Stephan; Eischeid, Carter J.; Leyhe, Martin J.; Nelson, Erika N.; Rahic-Seggerman, Faith M.; Sullivan, Kasey E.; Peters, Nick T. (Frontiers in Microbiology, 2022)
Soft rot disease causes devastating losses to crop plants all over the world, with up to 90% loss in tropical climates. To better understand this economically important disease, we isolated four soft rot-causing Erwinia persicina strains from rotted vegetables. Notably, E. persicina has only recently been identified as a soft rot pathogen and a comprehensive genomic analysis and comparison has yet to be conducted. Here, we provide the first genomic analysis of E. persicina, compared to Pectobacterium carotovorum, P. carotovorum, and associated Erwinia plant pathogens. We found that E. persicina shares common genomic features with other Erwinia species and P. carotovorum, while having its own unique characteristics as well. The E. persicina strains examined here lack Type II and Type III secretion systems, commonly used to secrete pectolytic enzymes and evade the host immune response, respectively. E. persicina contains fewer putative pectolytic enzymes than P. carotovorum and lacks the Out cluster of the Type II secretion system while harboring a siderophore that causes a unique pink pigmentation during soft rot infections. Interestingly, a putative phenolic acid decarboxylase is present in the E. persicina strains and some soft rot pathogens, but absent in other Erwinia species, thus potentially providing an important factor for soft rot. All four E. persicina isolates obtained here and many other E. persicina genomes contain plasmids larger than 100 kbp that encode proteins likely important for adaptation to plant hosts. This research provides new insights into the possible mechanisms of soft rot disease by E. persicina and potential targets for diagnostic tools and control measures.